Long Term Testing of Solid Oxide Electrolysis Cells under Co-Electrolysis Conditions. (31st August 2017) - Rao, Megha; Sun, Xiufu; Hagen, Anke
Abstract : SOECs consisting of a nickel-yttria stabilized zirconia (Ni-YSZ) fuel electrode, YSZ electrolyte and lanthanum strontium cobalt ferrite-gadolinium doped ceria (LSCF-GDC) composite oxygen electrode were tested under co-electrolysis (H2 O+CO2 ) conditions. The aim in this study was to compare the SOEC durability under co-electrolysis conditions between galvanostatic and potentiostatic modes. Specifically, the cells were operated at 0.75 A/cm 2 (galvanostatic) and at 1.2 V (potentiostatic) at 750 o C for over 1000 hours. In both modes, a larger degradation was observed initially for the first 200 hours of testing, followed by a more stable performance over longer operating times. Trends of the area specific resistance (ASR) and detailed electrochemical analysis of the cell's performance under durability conditions for both modes indicated that the degradation was predominantly due to the fuel electrode along with a slight contribution from the oxygen electrode. Microstructural analysis also confirmed the degradation of the active fuel electrode.